Literature, Rhetoric, and Culture: Lessons from Iceland, Manitoba, and Minnesota (2020-12-02) - Beard, David; University of Minnesota Duluth. Royal D. Alworth, Jr. Institute for International Studies (2020)
Wednesday, December 2, 2020, 12:00 to 2:00 pm (there will be a brief break); Hosted by Dr. David Beard, Professor, UMD Department of English, Linguistics, and Writing Studies; Free and open to the public; A LSBE & CLA Passport Event In a series of presentations, scholars from Iceland and Canada will discuss literature, sagas and artistic expressions that connect these areas and Minnesota. They will explore shared values rooted in the Medieval and Viking ages. Specific topics include: "Attracting Readers for Eight Centuries: The Icelandic Sagas"; "The Afterlife of Eddas and Sagas in Popular Culture"; "Hitting the Road: Icelandic Fiction in the 21st Century"; "Vikings in Gimli"; and, "Taming Settler Colonialism: The Statue of Lieutenant Harry Colebourn and Winnie-the-Bear." Funding provided by the Carol Pazandak Iceland-Minnesota Travel Fund of the Global Programs and Strategies Alliance, and sponsored by the UMD Program in Writing Studies and the Alworth Institute